The Book of Garden Management - Anonymous (Cambridge library collection. Botany and Horticulture, 1871)
This anonymous work (the name of H. P. D., the author of the preface, is not known) was probably compiled by Samuel Orchart Beeton (1831–77), the publishing entrepreneur who made his wife's Book of Household Management one of the best-selling titles of the century. Published in 1871, it is a complete guide to gardening for the enthusiastic middle-class amateur, with instructions on everything from choosing the site to garden design, plants and cultivation, 'fountains, fish-ponds, and ornamental waters' to the use of colour, interspersed with a detailed calendar of tasks to be carried out each month. It is illustrated with line engravings and twelve plates (which can be viewed in colour online at http:www.cambridge.org/9781108049399), providing both practical information and a fascinating insight into the plants available to the Victorian gardener, the techniques for cultivating flowers, fruit and vegetables, and the then current trends in design and display